Influence of Work Facilities, Competency, Communication on Business Participants' Satisfaction Through Service Quality as a Variable Intervening at Investment and One Door Opening Service of the Province of the Riau Island Government - Lili Hendrayani; Chablullah Wibisono; Bambang Satriawan (LPPM STIE Krakatau, 2025)
Purpose: This study analyzes the effects of work facilities, competence, and communication on business satisfaction through service quality at the Riau Islands Investment and One-Stop Integrated Service Office. Research Methodology: This quantitative study involved all 168 employees of the Riau Islands Investment and One-Stop Integrated Service Office, using a saturated (census) sampling technique and Partial Least Squares (PLS) analysis with SmartPLS 4.0. Results: Work facilities and service quality significantly affect satisfaction, while competence and communication show positive but insignificant effects. Service quality also mediates the effects of competence and communication on satisfaction but not work facilities. Conclusions: Work facilities and service quality significantly affect business participants’ satisfaction, while competence and communication have positive but insignificant effects. Service quality mediates the effects of competence and communication on satisfaction but not work facilities. Limitations: This study is limited to one government office with a cross-sectional design and excludes other factors like leadership and motivation. Contribution: This study confirms service quality’s mediating role and provides guidance to enhance satisfaction through improved facilities, competence, and communication.